Novel Dry Hyaluronic Acid-Vancomycin Complex Powder for Inhalation, Useful in Pulmonary Infections Associated with Cystic Fibrosis - María S. Magi; Yanina de Lafuente; Eride Quarta; María C. Palena; Perla del R. Ardiles; Paulina L. Páez; Fabio Sonvico; Francesca Buttini; Alvaro F. Jimenez-Kairuz (MDPI AG, 2024)
Polyelectrolyte-drug complexes are interesting alternatives to improve unfavorable drug properties. Vancomycin (VAN) is an antimicrobial used in the treatment of methicillin-resistant Staphylococcus aureus pulmonary infections in patients with cystic fibrosis. It is generally administered intravenously with a high incidence of adverse side effects, which could be reduced by intrapulmonary administration. Currently, there are no commercially available inhalable formulations containing VAN. Thus, the present work focuses on the preparation and characterization of an ionic complex between hyaluronic acid (HA) and VAN with potential use in inhalable formulations. A particulate-solid HA-VAN25 complex was obtained by spray drying from an aqueous dispersion. FTIR spectroscopy and thermal analysis confirmed the ionic interaction between HA and VAN, while an amorphous diffraction pattern was observed by X-ray. The powder density, geometric size and morphology showed the suitable aerosolization and aerodynamic performance of the powder, indicating its capability of reaching the deep lung. An in vitro extended-release profile of VAN from the complex was obtained, exceeding 24 h. Microbiological assays against methicillin-resistant and -sensitive reference strains of Staphylococcus aureus showed that VAN preserves its antibacterial efficacy. In conclusion, HA-VAN25 exhibited interesting properties for the development of inhalable formulations with potential efficacy and safety advantages over conventional treatment.